Long-term survival outcomes of esophageal squamous cell carcinoma with intraoperative thoracic duct ligation: a large-scale propensity score matching analysis - Ke-xun Li; Ke-xun Li; Si-miao Lu; Si-miao Lu; Chang-ding Li; Chang-ding Li; Cheng-hao Wang; Jia-hua Lv; Jia-hua Lv; Qi-feng Wang; Qi-feng Wang; Yun-chao Huang; et al. (Frontiers in Oncology)
BackgroundEsophagectomy is the primary treatment for localized esophageal squamous cell carcinoma (ESCC). Intraoperative thoracic duct ligation (TDL) has been suggested as an adjunct to reduce the risk of postoperative chylothorax in patients with ESCC, but its effect on long-term oncologic outcomes remains uncertain.MethodsData from the Sichuan Cancer Hospital and Institute Esophageal Cancer Case Management Database were analyzed for patients treated between 2010 and 2017. Participants were classified into TDL and non-TDL groups. Univariate Cox regression analyses and propensity score matching (PSM) were used to identify independent risk factors for overall survival (OS).ResultsA total of 2,510 patients were included, with 2,095 in the TDL group and 415 in the non-TDL group. The median follow-up was 63.97 months. No significant differences in OS were observed between the TDL and non-TDL groups (HR: 1.13; 95% CI: 0.96–1.31; P = 0.13). After PSM, the analysis continued to show no significant differences between the groups (P = 0.72).ConclusionIntraoperative TDL during esophagectomy did not significantly impact long-term OS in patients with ESCC.